Rapid Prototyping of Heterogeneous Objects: Issues and Challenges - Gupta, Vikas; Bala, Rajni; Garg, Ashok Kumar; Ranjan, Rajeev Kumar (Asian Review of Mechanical Engineering, 2016)
Heterogeneous objects (HO), composed of multiple materials, are now increasingly being used in engineering applications. With the development of a new fabrication method called Rapid Prototyping (RP), a new dimension is added to manufacture these objects. To manufacture heterogeneous object by RP, a CAD model is required that contains both geometric information as well as material information. Conventionally, most of the available CAD modelling software are able to save the 3D modelled object in the form of geometric and topologic data in stereo lithography file format and do not contain local information of the different materials or their composition in the object. So the conventional 3D modelling software can not be used for the fabrication of heterogeneous objects (HO) through rapid prototyping. The paper highlights all these issues and problems which arise for rapid prototyping of heterogeneous objects. The principles of rapid manufacturing for homogenous objects are discussed and various available RP techniques are explored. The procedure for rapid manufacturing of heterogeneous objects has been proposed. Various challenges and issues are highlighted. Finally, based on these issues, the objectives and scope for future work are identified.